2020
DOI: 10.18805/lr-4213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Invigouration on Yield Enhancement in Grain Cowpea Vigna unguiculata (L.) Walp

Abstract: Field experiment was conducted at Coconut Research Station, Balaramapuram with an objective to assess the effect of seed invigouration with zinc sulphate and borax on grain cowpea and to evaluate its effect along with Trichoderma viride on field emergence, growth, yield attributes and yield of the crop. Field emergence percentage was significantly influenced by seed invigouration and an enhancement in the germination percentage of 20.54 to 27.79 was observed compared to control. Seed priming with ZnSO4 @ 0.05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Addition of organic matter through FYM and decomposition of fallen leaves from the cowpea plant also paved for better availability of nutrients. Similar observations were also made by Raj (2019) in cowpea. Lower P uptake by the crop resulted in higher post-harvest P status in T 1 .…”
Section: Effect On Post-harvest Nutrient Statussupporting
confidence: 88%
“…Addition of organic matter through FYM and decomposition of fallen leaves from the cowpea plant also paved for better availability of nutrients. Similar observations were also made by Raj (2019) in cowpea. Lower P uptake by the crop resulted in higher post-harvest P status in T 1 .…”
Section: Effect On Post-harvest Nutrient Statussupporting
confidence: 88%
“…Foliar application of ZnSO 4 0.05 per cent increased the Zn uptake from 18 to 37 per cent (Purushottam et al, 2018). Grain cowpea seeds primed in 0.05 per cent ZnSO 4 for 4 h recorded higher total uptake of N, P and K by crop (Raj, 2019).…”
Section: Effect Of Zn and B Nutrition On Nodulation In Pulsesmentioning
confidence: 89%
“…Debnath et al (2018) who observed that application of B along with recommended dose of fertilizers increased the B uptake in grain cowpea. Raj (2019) observed that seed pelleting with borax significantly improved the B uptake in grain cowpea compared to control and it was also observed that compared to seed pelleting with 50 mg borax kg -1 seed, 100 mg borax kg -1 seed recorded higher uptake of B. Seema et al (2014) reported that N content in seeds significantly increased with the application of Zn in green gram.…”
Section: Effect Of Zn and B Nutrition On Nodulation In Pulsesmentioning
confidence: 90%
See 1 more Smart Citation
“…Jyothi and Hebsur (2017) reported that application of nano fertilizers may help in slow and steady release of nutrients and it also minimize the loss of nutrients and improves nutrient use efficiency. Also, Raj et al (2019) reported that application of Zinc sulphate nano particle as seed priming invigoration improved the seedling growth and establishment. The right seed coating plays a major role, wherein every coated seed has the opportunity to fulfil its Influence of Nano Formulation on Augmenting the Seed Quality in Groundnut (Arachis hypogaea L.) potential, which could be achieved through encapsulation of seeds with bioactive inputs incorporated nanoformulation.…”
Section: Introductionmentioning
confidence: 99%